Transcatheter transseptal mitral valve implantation with Edwards SAPIEN 3: the first experience of a single center - Kralisz, Paweł; Frank, Marek; Sobkowicz, Bożena; Dobrzycki, Slawomir; Hirnle, Tomasz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
In recent years, there has been a clear trend towards increased mitral bioprosthetic valve surgery in comparison to mechanical prostheses [1]. According to the ESC Guidelines mitral bioprostheses are recommended for patients > 70 years old or those with a life expectancy lower than the presumed durability of the bioprosthesis (class IIa/C). Importantly, the guidelines also recognize the prominence of quality of life after cardiosurgery and focus on patients’ preferences (class Ic), especially if long-term anticoagulation is nonoptimal (class Ic) [2]. Structural deterioration of mitral bioprostheses (structural valve deterioration – SVD) is the main limitation for their use. The average lifespan of a bioprosthetic valve is estimated at 16 years and the reoperation due to SVD affects as many as 75% of patients after a 20-year follow-up [3, 4]. Reoperation is usually associated with high risk of complications and mortality [5, 6].